2003
DOI: 10.1007/s00535-003-1139-2
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose azathioprine is effective and safe for maintenance of remission in patients with ulcerative colitis

Abstract: A dose of 50 mg/day of AZA is effective and safe for maintenance of remission in the Japanese population. Investigation of the TPMT allele may be useful for predicting the appearance of bone marrow suppression, when low-dose 6-MP or AZA is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
117
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 26 publications
(41 reference statements)
10
117
0
Order By: Relevance
“…TPMT activity is reported to depend on the genetic polymorphism of high-versus lowmetabolizing alleles (5,6) (13). In this study, we found TPMT*3C mutation in 0.9% of the Japanese population, and this is similar to the observations by Kubota et al (11,14).…”
Section: Discussionsupporting
confidence: 90%
“…TPMT activity is reported to depend on the genetic polymorphism of high-versus lowmetabolizing alleles (5,6) (13). In this study, we found TPMT*3C mutation in 0.9% of the Japanese population, and this is similar to the observations by Kubota et al (11,14).…”
Section: Discussionsupporting
confidence: 90%
“…In particular, Japanese populations are sensitive to thiopurines, and relatively lower doses of AZA (0.6-1.2 mg/kg/day) are recommended for the treatment of Japanese IBD patients (11). Similar to TPMT A719G and ITPase C94A, we recently showed that MRP4 G2269A is a new factor accounting for heightened thiopurine sensitivity in Japanese patients with IBD (24).…”
Section: Discussionmentioning
confidence: 96%
“…However, in 15-30% of patients, these drugs have to be discontinued due to adverse effects including bone marrow suppression, hepatotoxicity, pancreatitis, fever, rash and gastrointestinal intolerance (4)(5)(6)(7)(8)(9). Furthermore, an AZA dosage of 2-3 mg/kg is recommended for the treatment of IBD patients in Western countries (10), but lower doses of AZA (0.6-1.2 mg/kg/day) are used in Japanese patients due to their relatively heightened sensitivity (11).…”
Section: Introductionmentioning
confidence: 99%
“…The high expression of P-gp in the peripheral blood lymphocytes of patients with systemic lupus erythematosus resulted indecreased lymphocyte glucocorticoid levels, steroid-resistance, and reduced efficacy (Hibi et al, 2003). A study by Wasilewska et al (2007) also showed that steroid-resistance or -dependence in children with nephrotic syndrome was related to P-gp expression in peripheral lymphocytes.…”
Section: Discussionmentioning
confidence: 99%